Effect of Triphaladi Choornam Mouthwash and Chlorhexidine Gluconate Mouthwash in Radio-Chemotherapy Induced Oral Mucositis in Non Metastatic Squamous Cell Carcinoma of Head and Neck: A Comparative Study - Nair, Sruthi; Gokul, R; Hameed, Thanweer; Madhumida; Saravanan, G (International Research Journal of Ayurveda & Yoga, 2023)
Background: The cases of lung and mouth cancer have boomed in the last decade due to various reasons, the major one being tobacco consumption. In non-metastatic squamous cell cancer of the head and neck, oral mucositis becomes prominent, especially during chemo or radiotherapy. Such patients also often suffer from stomatitis, xerostomia and pharyngitis. Materials and methods: This comparative study comprises of 36 patients undergoing chemo and radiotherapy. Here, 18 patients each are randomly allocated in two groups. One group receiving the existing prophylactic treatment i.e., chlorhexidine gluconate mouthwash and the other group received, Triphaladi choornam for gargling. Both the groups were asked to perform gargling, from the first day of radiation therapy to 21 days thereafter. Analytical tools: The effectiveness of both mouthwashes was compared for their healing potential and quality of life by WHO oral mucositis scale and Patient Reported Oral Mucositis Symptoms (PROMS)scale respectively. Conclusion: The reduction in mucositis and betterment of quality of life was significant in the group which received ayurvedic mouthwash compared to the prophylactic treatment group.